Measuring instrument management in ISO quality management system environment - Lua, Kheng Leong (2020)
Measuring instrument accuracy and consistently meeting measurement accuracy are the two main issues of argument especially when product conformity is based on the measured results ultimately affect organisation profit. ISO quality management systems required measuring instrument to meet requirements; however, there is no specific instruction on how to determine measuring instrument is fit for purpose and continuously to do so. The practices become individualistic and apparently lack of monitoring mechanism to prove that these methods could statistically and or logically justified.